VEGETATION BURIED UNDER DAWSON TEPHRA (25,300 14C YEARS BP) AND LOCALLY DIVERSE LATE PLEISTOCENE PALEOENVIRONMENTS OF GOLDBOTTOM CREEK, YUKON, CANADA - Zazula G.D.; Mathewes R.W.; Froese D.G.; Reyes A.V.; Elias S.A.; Kuzmina S.; La Farge C.; Sanborn P.T.; Schweger C.E.; Scott Smith C.A. (My University, 2006)
Paleoecological research at Goldbottom Creek in the Klondike region of Yukon Territory (NW Canada) documents an in situ riparian grassy meadow that was buried during the winter or early spring by Dawson tephra, near the onset of Marine Isotope Stage (MIS) 2, ca. 25,300 14C years BP. Analyses of vascular plant macrofossils, bryophytes, pollen, insects and paleosols from the riparian meadow contrast with evidence for well-drained, upland steppe-tundra habitats obtained from fossil arctic ground squirrel middens within the same valley. The mesic valley bottom vegetation consisted of grasses (Deschampsia caespitosa, Alopecurus), sedges (Carex), horsetail (Equisetum cf. palustre), diverse bryophytes and few forbs. Upland habitats with dry loessal soils along the valley slopes contained graminoids (Elymus, Festuca, Kobresia myosuroides), sage (Artemisia frigida) and diverse steppe and tundra forbs (Phlox hoodii, Plantago cf. canescens, Anemone patens var. multifida, Bistorta vivipara, Draba). These paleoecological data highlight the effect of topographic position and moisture on substrates and their control on local-scale habitat variability. This study represents the first recorded in situ riparian surface from the unglaciated Pleistocene refugium of Beringia and provides well-documented evidence for local habitat heterogeneity and ecosystem structure within the mammoth-steppe biome. Other radiocarbon dated paleoecological data from our study sites indicate that full-glacial steppe-tundra habitats in west-central Yukon Territory were established during the later stages of the MIS 3 interstadial, by 29,000 14C years BP. The diverse data obtained through integration of multiple paleoecological methods at the site demonstrate the efficacy of interdisciplinary research in furthering our understanding of Beringian glacial environments. © 2006 Elsevier B.V. All rights reserved.
Keywords: BERINGIA; KLONDIKE; PALEOECOLOGY; TEPHRA; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен